2009
DOI: 10.1128/aac.00789-09
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Pulmonary [ 18 F]-2-Fluoro-Deoxy- d -Glucose Positron Emission Tomography Correlates with Bactericidal Activity of Tuberculosis Drug Treatment

Abstract: Tools for monitoring response to tuberculosis (TB) treatment are time-consuming and resource intensive. Noninvasive biomarkers have the potential to accelerate TB drug development, but to date, little progress has been made in utilizing imaging technologies. Therefore, in this study, we used noninvasive imaging to monitor response to TB treatment. BALB/c and C3HeB/FeJ mice were aerosol infected with Mycobacterium tuberculosis and administered bactericidal (standard and highly active) or bacteriostatic TB drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
141
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(148 citation statements)
references
References 23 publications
5
141
0
Order By: Relevance
“…Using an animal model and TB infection model, it has been shown that quantitative 18 F-FDG uptake can be used to monitor the effectiveness of treatment. 115,140 In this study, there was a clear correlation between the fall in 18 F-FDG uptake in the lungs and successful administration of a bactericidal drug. In contrast, uptake of 18 F-FDG increased when an ineffective drug was given and in the control group.…”
Section: Therapy Monitoring Of Tbmentioning
confidence: 84%
“…Using an animal model and TB infection model, it has been shown that quantitative 18 F-FDG uptake can be used to monitor the effectiveness of treatment. 115,140 In this study, there was a clear correlation between the fall in 18 F-FDG uptake in the lungs and successful administration of a bactericidal drug. In contrast, uptake of 18 F-FDG increased when an ineffective drug was given and in the control group.…”
Section: Therapy Monitoring Of Tbmentioning
confidence: 84%
“…C3HeB/FeJ mice are highly susceptible to M. tuberculosis infection, and develop necrotic granulomas in which the bacilli are exposed to hypoxic conditions (33,34). In contrast, C3H/HeJ mice do not develop necrosis, and the majority of bacilli appear to reside intracellullarly by histologic assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculous lesions can be detected by 18 F-fluorodeoxyglucose with positron emission tomography coregistered with computed tomography (FDG PET/CT) in several animal models of tuberculosis, including the nonhuman primate, although this has mostly been reported in the context of drug efficacy studies (2)(3)(4). The use of PET/CT facilitates real-time, serial in vivo assessments of disease progression without the need for sacrificing experimental animals.…”
mentioning
confidence: 99%